2018
DOI: 10.1007/s12011-018-1415-x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals in the Freshwater Fish Cyprinus carpio: Effect to Serum Biochemistry and Oxidative Status Markers

Abstract: Interactions between trace metals, serum biochemical parameters, and oxidative status markers were observed. Freshwater fish Cyprinus carpio blood samples (n = 38) were collected at the beginning of May (n = 19) and at the end of July (n = 19) of 2015. The concentrations of metals (As, Cd, Cr, Cu, Fe, Mn, Ni, Pb, Se, Sr, and Zn) were analyzed in blood serum samples of fishes by inductively coupled plasma optical emission spectrometry (ICP-OES), and Hg was determined by cold-vapor atomic absorption spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Uric acid was found to decrease under arsenic stress on C. gariepinus of the present work and that of Ogamba et al (2011). Different other studies revealed an increase in uric acid under arsenic stress (Kumari, 2015) and different other pollutants (Mutlu et al, 2015;Kovacik et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…Uric acid was found to decrease under arsenic stress on C. gariepinus of the present work and that of Ogamba et al (2011). Different other studies revealed an increase in uric acid under arsenic stress (Kumari, 2015) and different other pollutants (Mutlu et al, 2015;Kovacik et al, 2019).…”
Section: Discussionmentioning
confidence: 84%
“…Biochemical blood factors are diagnostic tools for evaluating the metabolic rate (blood protein and globulin), kidney function (creatinine, bilirubin, and uric acid), liver function (albumin, ALT, AST, and ALP), and stress indices (cortisol and glucose) of the organism [ 49 , 50 ]. Under toxicity conditions, the levels of these indices may deteriorate, referring to dysfunction of vital organs involved in renal, metabolic, antioxidative, and immunity roles in the fish body [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…For analysis of cortisol DIALAB Elisa test kit (DIALAB Pruduktion and Vertrieb von chemish – technischen Produkten und Laborinstrumenten Gesellschaft m. b. H., Wiener Neudorf, Austria) was used. Mineral profile analysis was measured using commercial DiaSys (Diagnostic Systems GmbH, Holzheim, Germany) on the Randox RX Monza analyser (Crumlin, United Kingdom) ( Kováčik et al, 2017 , Kovacik et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%